LaTeX Fadne (3)

1 Name: Ernst : 2018-10-31 17:55 [Del]

\title{Sample Proof Using Mathematical Induction}
\author{Brandon Grasley}

\\For any $n \in \mathbb{N}$,
\[$\sum_{i=1}^{n}i=\frac{n\left ( n+1 \right )}{2}$\]
\\Base case $n=1$: If $n=1$, the left side is 1 and the right side is $\frac{1\left ( 2\right )}{2}=1$.
So, the theorem holds when $n=1$.
Inductive hypothesis: Suppose the theorem holds for all values of $n$ up to some $k$, $k \geq 1$.
Inductive step: Let $n=k+1$. Then our left side is
$\sum_{i=1}^{k+1}i&=\left (k+1\right )+\sum_{i=1}^{k}i\\
&=\left (k+1\right )+\frac{k\left ( k+1 \right )}{2}$\text{, by our inductive hypothesis}\\
$&=\frac{2\left (k+1 \right )}{2}+\frac{k\left (k+1 \right )}{2}\\
&=\frac{2\left (k+1 \right )+k\left (k+1 \right )}{2}\\
&=\frac{\left (k+1 \right )\left (k+2\right )}{2}$
which is our right side. So, the theorem holds for $n=k+1$.
By the principle of mathematical induction, the theorem holds for all $n \in \mathbb{N}$.

2 Post deleted by moderator.

3 Name: Anonymous : 2018-11-11 17:18 [Del]

TeX is cheating.
π•·π–†π•Ώπ–Šπ–ƒ π–œπ–Šπ–Œπ–‡π–šπ–π–Šπ–“

Name: Link:
Leave these fields empty (spam trap):
More options...